Sarcoidosis-related mortality in France: a multiple-cause-of-death analysis. Issue 6 (22nd September 2016) - Jamilloux, Yvan; Maucort-Boulch, Delphine; Kerever, Sébastien; Gerfaud-Valentin, Mathieu; Broussolle, Christiane; Eb, Mireille; Valeyre, Dominique; Seve, Pascal
We evaluated mortality rates and underlying causes of death among French decedents with sarcoidosis from 2002 to 2011. We used data from the French Epidemiological Centre for the Medical Causes of Death to 1) calculate sarcoidosis-related mortality rates, 2) examine differences by age and gender, 3) determine underlying and nonunderlying causes of death, 4) compare with the general population (observed/expected ratios), and 5) analyse regional differences. 1662 death certificates mentioning sarcoidosis were recorded. The age-standardised mortality rate was 3.6 per million population and significantly increased over the study period. The mean age at death was 70.4 years ( versus 76.2 years for the general population). The most common underlying cause of death was sarcoidosis. Sarcoidosis decedents were more likely to be males when aged <65 years. When sarcoidosis was the underlying cause of death, the main other mentions on death certificates were chronic respiratory and cardiovascular diseases. The overall observed/expected ratio was >1 for infectious disease, tuberculosis and chronic respiratory disease, and <1 for neoplasms. We observed a north–south gradient of age-standardised mortality ratio at the country level. Despite the limitation of possibly capturing the more severe cases of sarcoidosis, this study may help define and prioritise preventive interventions. Information from death certificates improves knowledge on sarcoidosis-related mortality http://ow.ly/1g1a302XxjQ